2001
DOI: 10.1002/1521-396x(200112)188:4<1443::aid-pssa1443>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Reflection Anisotropy Spectroscopy as a Probe of Molecular Assembly on Metal Surfaces

Abstract: The potential of the optical technique of Reflection Anisotropy Spectroscopy (RAS) as a probe of molecular assembly on metal surfaces is described. It is shown that RAS can be used to monitor the growth of molecular layers on both disordered and ordered substrates though work in the later regime is at an early stage. The strengths and weaknesses of RAS as a probe of surface order are described and attention is drawn to the importance of morphological changes in surface order due to molecular substrate interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…RAS is a local probe that depends on macroscopic anisotropy. The intensity of a feature in the RA spectrum is a product of the intrinsic strength of the feature, the number of sites and the degree of anisotropy of the surface . The sensitivity of the RAS profiles to the morphology of Au(110) surfaces is due to the dependence of the signal strength on both the local atomic structure and the macroscopic anisotropy of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…RAS is a local probe that depends on macroscopic anisotropy. The intensity of a feature in the RA spectrum is a product of the intrinsic strength of the feature, the number of sites and the degree of anisotropy of the surface . The sensitivity of the RAS profiles to the morphology of Au(110) surfaces is due to the dependence of the signal strength on both the local atomic structure and the macroscopic anisotropy of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In this work we present the results of studies of adenine adsorbed at Au͑110͒/electrolyte interfaces using reflection anisotropy spectroscopy ͑RAS͒, which is a surface sensitive optical technique that can provide information on the orientation of molecules adsorbed at interfaces. [7][8][9][10][11][12][13][14][15][16][17][18][19] Initial studies of adenine adsorbing onto mercury electrodes showed that the adenine molecule undergoes a phase transition from planar to vertical as the potential is changed. 20,21 There have been a number of electrochemical studies of the adsorption of adenine on the Au͑111͒ and Au͑100͒ surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the RAS experiment is selected so as to yield an optical probe of a surface, provided that the structure of the sample satisfies certain criteria. 14 For cubic crystal structures, for instance, the RAS contribution from the bulk cancels by symmetry and RAS will yield the optical response of the surface provided that the surface has a C 2 axis of symmetry. For a perfectly amorphous material, the bulk RAS will also cancel and RAS will essentially be an optical probe of the surface, which may, or may not, yield a non-zero signal depending on its symmetry.…”
Section: Reflection Anisotropy Spectroscopy Methodologymentioning
confidence: 99%